Pengaruh Persepsi Produk dan Sikap Konsumen Terhadap Keputusan Pembelian Mie Instan Samyang DiIndomaret Mardani Jakarta Pusat - Nur Hurriyah; Mercy Spesa Devina De Fretes (JAMBIS : Jurnal Administrasi Bisnis, 2022)
The study was descriptive quantitative with the purpose of analyzing the factors that affect the purchase decision of Samyang instant noodles at Indomaret Mardani, Central Jakarta. Based on the results of the study, it was found that Product Perception affected the Purchase Decision of Samyang Instant Noodles by 45.5%, the remaining 54.5% was affected by other variables not analyzed in this study. The consumer attitude affected the purchase decision of Samyang Instant Noodles by 39.4%, the remaining 60.6% was affected by other variables not analyzed in this study. The results also indicated that the Product Perception and Consumer Attitude affected the Purchase Decision of Samyang Instant Noodle by 48.2%, the remaining 51.8% was affected by other variables not analyzed in this study.